Bronhoskopska igelna aspiracija povečanih mediastinalnih bezgavk s pomočjo endobronhialnega ultrazvoka - Triller, Nadja (Zdravniški vestnik, 2005)
Background. Conventional transbronchial needle aspiration TBNA) of enlarged mediastinal lymph nodes is a fairly blind technique. Endobronchial ultrasound (EBUS) guided TBNA resulted in higher success rate. T'he needle can be inserted safely into the lymph node. We examined the diagnostic yield of EBUS guided TBNA in clinical circumstances. Patients and methods. Patients with enlarged mediastinal lymph nodes, detected on chest X-ray and/or CT' scan, underwent bronchoscopy. The exact location of lymph nodes was established by EBUS. 20 MHz ultrasound probe with a balloon catheter was used. Results. Seventy five patients aged between 20 and 79 years (median age 55 years), underwent EBUS examination followed by TBNA of the target lymph node. Lymph nodes pathology was correctly diagnosed in 65 (87%) of them. In 52 (70%) patients the lymph nodes were infiltrated with malignoma, 13 (17%) had benign diseases and in 10 (13%) patients with non definitive disease the final diagnosis was obtained by surgery or by follow up. No major complication was encountered after EBUS-guided TBNA.
Keywords: Biopsija igelna; Biopsy, Needle; Bronchoscopy; Bronhoskopija; diagnostika; Limfatična metastaza; Lung Neoplasms; Lymphatic Metastasis; Mediastinum; Pathology; Pljučne novotvorbe; Ultrasonography; ultrasound; ultrazvok